Estimate Effects of Reinforced Plain 2D-Woven Fabric Crimp on Elastic Constants of Geo-Composite by Analytical Models: Published online: 10/03/2026 - Phan, Thanh Nhan (Journal of Technical Education Science, 2026)
One important aspect influencing the mechanical properties of the composite material is thought to be the undulation of the fiber bundles in the woven fabric structure, which is employed as the reinforcing phase for the composite plate with geo-polymer resin. The unidirectional, straight, non-corrugated thread in the composite material system behaves mechanically differently from the fabric that is created during the weaving process. Furthermore, the mechanical properties of composite materials are also greatly influenced by the interaction between the fiber and matrix. Thus, it is important from a scientific and practical standpoint to assess how the parameters that define the corrugated fabric affect the elastic mechanical properties of composite plates and the reciprocal interaction between the fiber and matrix. Developing a mathematical model and computation technique to estimate the effects of reinforced plain 2D-woven fabric crimp on elastic constants of geo-composite and investigating adhesion between geo-polymer and fiber are the main goals of this paper. The simulation's findings indicate that the geo-composite panels reinforced with plain woven fabrics and very small crimped have a negligible effect on the materials' elastic constants. These outcomes also align with the experimental results.